The infrastructure projects in the Caspian Region - S. S. Zhiltsov (Проблемы постсоветского пространства)
In recent years, the countries of the Caspian region have sought to expand regional cooperation in energy and transport spheres. For a long time, these areas of cooperation were not being developed, which negatively affected the regional economy. The revision of the existing approaches of regional countries to cooperation is dictated by the growth of problems of economic development of each country. Non-regional states have a continuing interest in the Caspian region. First of all, they are interested in projects aimed at diversifying the supply of hydrocarbon resources from the region to foreign markets. In turn, the construction of new export pipelines is considered by the countries of the Caspian region as a way of strengthening their geopolitical positions and realising socio-economic projects. New pipelines not only can create additional opportunities for the delivery of oil and gas from the region to foreign markets, but also can radically change the balance of power. This explains the increased attention to the issues of production and export of hydrocarbon resources.At the same time, the revision of the energy policy of the regional countries, which began in the 1990s, did not reduce their dependence on non-regional states that act as final consumers or transit countries for oil and gas. The construction of new pipelines broke Russia’s monopoly over the export of hydrocarbon resources from the regional countries to foreign markets. However, the decline of Russian influence was compensated by Iran and China, which got the opportunity to influence the regional countries through pricing mechanisms and volumes of purchased hydrocarbon raw materials. For this reason, the regional countries are in favor of a further increase in the number of new pipelines, believing that their construction will expand opportunities for oil and gas exports and will reduce dependence on neighboring states.